Pengaruh Penyesuaian Diri dan Dukungan Sosial terhadap Stres Akademik pada Santri Baru Pondok Pesantren Ibnu Kholdun Al-Hasyimi Besuki Situbondo - Nuraini; Fitriani, Aprilya (Fakultas Dakwah UIN KHAS Jember, 2023)
This study is motivated by new students who are confronted with different circumstances compared to their prior experiences before residing in a pesantren (Islamic boarding school). These varying circumstances prompt students to undergo changes and adapt to their new environment, occasionally resulting in stress, including academic stress. These disparities necessitate that students adjust to their surroundings. Furthermore, alongside adaptation, students also require social support to navigate the pressures of their social environment. The objective of this study is to ascertain how adaptation and social support impact the academic stress experienced by new students at Pondok Pesantren Ibnu Kholdun AL-Hasyimi in Besuki Situbondo. This study utilizes a quantitative methodology employing multiple linear regression analysis. Total sampling is employed due to the subject number being below 100, specifically encompassing 49 new students at Pondok Pesantren Ibnu Kholdun AL-Hasyimi in Besuki Situbondo. The preliminary findings of the study concerning the adaptation variable and academic stress, at a significance level of 0.01 (α = 1%), demonstrate a significance value of 0.001 < 0.01, indicating a negative correlation. Thus, H1 is accepted, suggesting a significant negative association between adaptation and academic stress. On the other hand, regarding the social support variable and academic stress, at a significance level of 0.1 (α = 10%), the value of 0.074 < 0.1 indicates a negative correlation. Thus, H2 is accepted, suggesting a significant negative influence between social support and academic stress among new students. This implies that as the level of social support increases, the level of academic stress decreases among new students at Pondok Pesantren Ibnu Kholdun AL-Hasyimi. Conversely, a lower level of social support corresponds to a higher level of academic stress among these students.